Electrical Stimultan sebagai Upaya Menurunkan Kadar Gula Darah Pasien Diabetes Mellitus Tipe II di Puskesmas Stabelan - Ganik Sakitri; Undari Nurkalis (Universitas Muhammadiyah Klaten, 2025)
The non-communicable disease that is the biggest cause of death is diabetes mellitus. One of the non-pharmacological therapies for diabetes sufferers is the use of electrical stimulants. The application of electrical stimulants to diabetes mellitus patients was carried out at the Stabelan Health Center with a One Group pretest posttest design. Samples were taken using purposive sampling techniques with 20 respondents. Research results There is a very strong correlation between GDS values before and after intervention, with a correlation coefficient of 0.993 and a probability value of 0.000. This strong correlation indicates a consistent relationship between the two measurements. These results can be interpreted that there is a difference in blood sugar levels before and after being given Electrical stimulants in diabetes mellitus patients at the Stabelan Health Center in Surakarta. The conclusion of this study is that there is a statistically significant difference between the average blood sugar levels before and after being given electrical stimulants